The effect of phlebotomy training on blood sample rejection and phlebotomy knowledge of primary health care providers in Cape Town: A quasi-experimental study - Mumtaz Abbas; Fidele K. Mukinda; Mosedi Namane (AOSIS, 2017)
Background: There is an increasing amount of blood sample rejection at primary health care facilities (PHCFs), impacting negatively the staff, facility, patient and laboratory costs. Aim: The primary objective was to determine the rejection rate and reasons for blood sample rejection at four PHCFs before and after a phlebotomy training programme. The secondary objective was to determine whether phlebotomy training improved knowledge among primary health care providers (HCPs) and to develop a tool for blood sample acceptability. Study setting: Two community health centres (CHCs) and two community day centres (CDCs) in Cape Town. Methods: A quasi-experimental study design (before and after a phlebotomy training programme). Results: The sample rejection rate was 0.79% (n = 60) at CHC A, 1.13% (n = 45) at CHC B, 1.64% (n = 38) at CDC C and 1.36% (n = 8) at CDC D pre-training. The rejection rate remained approximately the same post-training (p > 0.05). The same phlebotomy questionnaire was administered pre- and post-training to HCPs. The average score increased from 63% (95% CI 6.97‒17.03) to 96% (95% CI 16.91‒20.09) at CHC A (p = 0.039), 58% (95% CI 9.09‒14.91) to 93% (95% CI 17.64‒18.76) at CHC B (p = 0.006), 60% (95% CI 8.84‒13.13) to 97% (95% CI 16.14‒19.29) at CDC C (p = 0.001) and 63% (95% CI 9.81‒13.33) to 97% (95% CI 18.08‒19.07) at CDC D (p = 0.001). Conclusion: There is no statistically significant improvement in the rejection rate of blood samples (p > 0.05) post-training despite knowledge improving in all HCPs (p < 0.05).